Early life nutrition during the first 1000 days from a Malaysian perspective - Choong, Zc; Cheah, Fc (Penerbit UKM, 2023)
The first 1000 days of life, encompassing the period from conception to a child’s second birthday, represents a pivotal phase in human development. This review paper highlighted the importance of this critical window with a comprehensive analysis exploring the multifaceted impact of nutrition during the three distinct phases: the pregnancy-intrauterine period, early infancy-breastfeeding period, and early childhood-complementary feeding period. Within the pregnancy intrauterine period, the maternal body mass index emerges as a crucial factor, directly affecting the well-being of both mother and child. Optimal nutrition, including essential micronutrients such as folic acid, iron, iodine, and vitamin D, are imperative to mitigate the risk of neural tube defects and related disorders, which remain a concern in Malaysia. Exclusive breastfeeding during the initial six months of life is identified as a cornerstone of infant development, nurturing both the child’s cognitive abilities and immune system. Timely introduction of complementary foods is equally vital, acting as a safeguard against childhood obesity and undernutrition. This review paper provided an in-depth examination of the importance and critical role of nutrition in the first 1000 days of life. It further outlined the current status, recommended strategies and interventions to improve child nutrition during this crucial phase in the Malaysian context.